The conundrum of the West : reading the novels of Nicholas Hasluck. - Holliday, Brian (Curtin University, 1998)
The purpose of this thesis is to explore the ways in which Nicholas Hasluck's novels have been read in the past, and to develop an alternative interpretation which takes into account all Hasluck's narratives, reading them through the framework of current trends in literary and cultural theory. Hasluck is a Western Australian writer whose work takes seriously, while at the same time parodies, the institutions of both Western Australia and Western society.The initial section comprises three chapters, in which Hasluck's novels are read through the commonly used frameworks of the mystery-thriller genre and satire. The second part of the thesis, which covers four chapters, is a reading of Hasluck's narratives through the shift from modernism to postmodernism, drawing particularly on the work of theorists such as Linda Hutcheon, Michel Foucault and Brian McHale. This interpretation reveals how Hasluck's work increasingly uses the marginal, regional narratives of Western Australia to contest the mega-narratives of the West.The significance of this thesis is twofold. Firstly, this is currently the most in-depth examination of the work of a neglected Western Australian writer, and, secondly, the combining of Hasluck's literary themes and this thesis's critical framework provides a productive format for exploring issues of Western Australian history and literature.